Dampak Pandemi Covid dan Penerapan New Normal pada Kredit Bermasalah dan Profitabilitas Perbankan Di Indonesia - Tri Septyanto; Dewi Susilowati (Kosmik Hukum, 2022)
The COVID-19 pandemic has had a significant impact on the economy, and the banking industry is no exception. The impact of the pandemic on the banking industry, namely the decline in bank health. Various efforts have been made by the government to revive the banking industry, one of which is the issuance of OJK regulation Number 11/PJOK.03/2020 concerning "National Economic Stimulus as a Countercyclical Policy for the Impact of the 2019 Covid Spread". This study aims to compare the ratio of non-performing loans/financing (NPL/NPF) and banking profitability in Indonesia before and after the COVID-19 pandemic and the implementation of the new normal. The object of this research is the banking industry, both conventional and sharia in Indonesia, with an observation period of 12 months from November 2019-November 2020. The sampling method uses purposive sampling, namely sampling according to the research objectives, and produces a sample of 38 conventional banking and 33 Islamic banking. The method of analysis used paired sample t-test. The results of the analysis show that: 1) there are significant differences in non-performing loans (NPL) before and after the covid 19 pandemic for conventional banking but for Islamic banking there is no significant difference. 2) There is no significant difference in the profitability of conventional banks before and after the pandemic or the implementation of the new normal. 3) there is no significant difference in NPL/NPF after the Covid 19 pandemic and after the implementation of the new normal. The results of this study provide empirical evidence that banking restructuring policies in Indonesia to anticipate the impact of COVID-19 have not run optimally.Keywords: comparison, performance, non-performing financing, profitability, banking